IMPLEMENTASI KEBIJAKAN UNDANG-UNDANG NOMOR 24 TAHUN 2013 TENTANG ADMINISTRASI KEPENDUDUKAN DI DINAS KEPENDUDUKAN DAN PENCATATAN SIPIL KABUPATEN KUTAI KARTANEGARA - Akhmad Sarbini; Aji Ratna Kusuma; Achmad Djumlani (Magister Administrasi Publik FISIP Universitas Mulawarman, 2017)
This research aims to describe and analyze the policy implementation of Law number 24 Year 2013 on population administration at Population and Civil Registry Service of KutaiKartangera District thorough the process of Electronic Identity Card Issuance. The research findings showed that Population and Civil Registry Service of KutaiKartanegara District had implemented the policy stated in Law Number 24 year 2013 on Population Administration, in the form of electronic ID Card issuance. However, its implementation was not optimal, which was indicated by the fact that there were still a lot of people who did not possess residency document, namely electronic ID Card.